1996
DOI: 10.1007/bf03192263
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopiazonic acid and aflatoxins production byAspergillus flavus isolated from Argentinian corn

Abstract: Thirty-four isolates ofAspergillus flavus obtained from the main Argentinian corn production area were tested for their ability to produce both cyclopiazonic acid (CPA) on corn and on liquid media and aflatoxins on corn.Aflatoxins and CPA were quantified by comparison with standards. The last one was confirmed by mass spectrometry.All but one of the isolates produced CPA on liquid medium in a range between 3120 to 62500 μg/kg, 27/34 isolates produced CPA on corn at levels ranging from 833 to 10000 μg/kg and 5/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…For testing aflatoxin B 1 (AFB 1 ), aflatoxin B 2 (AFB 2 ), aflatoxin G 1 (AFG 1 ), and aflatoxin G 2 (AFG 2 ), rice media was inoculated with 50 μl of the conidial suspension of A. flavus and incubated for 1 week, at 25°C (Resnik et al 1996, Moltó et al 1997. Rice medium was prepared with distilled water added with up to 40 % of polished rice in 250 ml Erlenmeyers, and autoclaved at 121°C for 30 min.…”
Section: Strains Culture Conditions and Mycotoxin Inductionmentioning
confidence: 99%
“…For testing aflatoxin B 1 (AFB 1 ), aflatoxin B 2 (AFB 2 ), aflatoxin G 1 (AFG 1 ), and aflatoxin G 2 (AFG 2 ), rice media was inoculated with 50 μl of the conidial suspension of A. flavus and incubated for 1 week, at 25°C (Resnik et al 1996, Moltó et al 1997. Rice medium was prepared with distilled water added with up to 40 % of polished rice in 250 ml Erlenmeyers, and autoclaved at 121°C for 30 min.…”
Section: Strains Culture Conditions and Mycotoxin Inductionmentioning
confidence: 99%
“…Different results were reported by Nesci and Etcheverry (2002) from preplanting maize soils, who reported a high percentage (82%) of nontoxigenic A. flavus. There is little data available on CPA potential producer A. flavus strains (Blaney et al 1989;Resnik et al 1996;Barros et al 2005). However, it is evident that a high percentage of the strains are potential producers of this mycotoxin.…”
Section: Aspergillus Section Flavi Toxigenic Capacitymentioning
confidence: 99%
“…The frequency of detection was 60% for the Caiapó, with mean levels ranging from 304.1 to 2583.7 μg/kg, and 74.3% for the 886, with levels ranging from 288.0 to 4918.1 μg/kg [17]. Other studies investigating the production of CPA in peanuts also reported high rates of 89 [52], 93 [53], and 97% [54]. Alatoxins and CPA were also detected simultaneously in kernel samples (11.4%).…”
Section: Resultsmentioning
confidence: 85%